EFEKTIVITAS PELAKSANAAN INOVASI TOR-TOR LIBAS TB DALAM UPAYA PENINGKATAN KEBERHASILAN PROGRAM DI UPTD PUSKESMAS PANYABUNGAN JAE KABUPATEN MANDAILING NATAL TAHUN 2022 - ., Erwinsyah; Sulistiana, Elvida; Br.Perangin-angin, Gina Kristina; Perangin-angin, Guntur; Iqbal, Muhammad; Siregar, Nurdin Yusuf; ariyani, peny; Lubis, Yulida Nehri (Deli Medical and Health Science Journal, 2024)
According to the World Health Organization (Global TB Report, 2021), Indonesia is still the country with the third largest burden of tuberculosis in the world after India and China and only 47% of cases are reported. and handled well. TOR Innovation TOR LIBAS TB is an innovation that aims to increase the scope of case finding and the success of TB treatment, the implementation of which involves cooperation from health workers, networks and networks, cross-program and sectoral and involves TB cadres in villages and sub-districts. The purpose of this study was to analyze the Effectiveness of Implementing TOR-TOR LIBAS TB Innovations in Efforts to Increase Program Success at UPTD Puskesmas Panyabungan Jae in 2022. The research design used the Mix-Method method with a Sequential Explanatory model. The number of informants was 14 people. Methods of data collection by in-depth interviews, focus group discussions, observation and review of documents and data analysis using triangulation were then integrated. Quantitative research results show the effectiveness of the coverage of TB case detection rates, namely with an average of 108 cases (37.56%) with Less Effective criteria, while the effectiveness of TB treatment success rate with an average of 70 cases (77.45%) with Effective criteria. Qualitative results show that the accuracy of program targets, achievement of program objectives, program monitoring, and satisfaction with the program are still not optimal, especially in the implementation of program socialization both to program implementers and the community. Regarding input availability of human resources, funds and infrastructure, it is still inadequate. Regulations/Standard Operational Procedures have been implemented, but have not been socialized properly. It is hoped that the puskesmas, cross-sectoral, the Health Service, will provide a role, support and increase cooperation and empower the community for the success of the program.